2011
DOI: 10.1017/s1743921312013282
|View full text |Cite
|
Sign up to set email alerts
|

Trigger Simulations for GRB Detection with the Swift Burst Alert Telescope

Abstract: Abstract. Understanding the intrinsic cosmic long gamma-ray burst (GRB) rate is essential in many aspects of astrophysics and cosmology, such as revealing the connection between GRBs, supernovae (SNe), and stellar evolution. Swift, a multi-wavelength space telescope, is quickly expanding the GRB category by observing hundreds of GRBs and their redshifts. However, it remains difficult to determine the intrinsic GRB rate due to the complex trigger algorithm adopted by Swift. Current studies of the GRB rate usual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…To investigate this issue further, a recent study by Lien et al (2012) performed a Monte Carlo analysis that generated a mock sample of GRBs, using the GRB rate and luminosity function of Wanderman & Piran (2010), and processed them through an entire simulated Swift detection pipeline, applying the full set of Swift trigger criteria, to determine which GRBs would be detected. It was found that the resulting measured GRB rate as a function of redshift followed very closely that of the true Swift GRB set described in Fynbo et al (2009); this finding is consistent with both the mock GRB sample and the simulated trigger pipeline being good approximations to reality.…”
Section: Classification: Identifying Gamma-ray Burstersmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate this issue further, a recent study by Lien et al (2012) performed a Monte Carlo analysis that generated a mock sample of GRBs, using the GRB rate and luminosity function of Wanderman & Piran (2010), and processed them through an entire simulated Swift detection pipeline, applying the full set of Swift trigger criteria, to determine which GRBs would be detected. It was found that the resulting measured GRB rate as a function of redshift followed very closely that of the true Swift GRB set described in Fynbo et al (2009); this finding is consistent with both the mock GRB sample and the simulated trigger pipeline being good approximations to reality.…”
Section: Classification: Identifying Gamma-ray Burstersmentioning
confidence: 99%
“…Our goal here is to replace the simulated Swift trigger pipeline with a classification NN, which (as we will see) can determine in just a few microseconds whether a given GRB is detected. To this end, we use as training data a pre-computed mock sample of 10, 000 GRBs from Lien et al (2012). In particular, we divide this sample randomly into ∼ 4000 for training, ∼ 1000 for validation, and the final ∼ 5000 as a blind test set on which to perform our final evaluations.…”
Section: Form Of the Classification Problemmentioning
confidence: 99%